Effect of active triangle and quartangle passing training on the accuracy of passing of men's participants futsal extracurricular - Danang Afrianto; Pipit Fitria Yulianto; Wisnu Mahardika; Ronny Suryo Narbito (Java Mutiara Media, 2024)
This study aims to determine the effect of active triangle passing and active rectangular passing training methods on the passing accuracy of men's futsal extracurricular participants at SMA Negeri 6 Surakarta. The type of research used in this research is an experiment using the research design